Enantioselective reduction of N-alkyl ketimines with frustrated Lewis pair catalysis using chiral borenium ions. Issue 49 (31st May 2019) - Mercea, Dan M.; Howlett, Michael G.; Piascik, Adam D.; Scott, Daniel J.; Steven, Alan; Ashley, Andrew E.; Fuchter, Matthew J.
Abstract : Effective enantioselective reduction of ketimines has been demonstrated by 'frustrated' Lewis pair catalysis using an IBiox-stabilised borenium cation. Abstract : Enantioselective reduction of ketimines was demonstrated using chiral N -heterocyclic carbene (NHC)-stabilised borenium ions in frustrated Lewis pair catalysis. High levels of enantioselectivity were achieved for substrates featuring secondary N -alkyl substituents. Comparative reactivity and mechanistic studies identify key determinants required to achieve useful enantioselectivity and represent a step forward in the further development of enantioselective FLP methodologies.